Estimasi Produksi Kopi Arabika Gayo Berdasarkan Crop Survey Petani Binaan CV. Bintang Musara Rasa Di Dataran Tinggi Tanoh Gayo. - M.P, Dr. Fadli; Sukanto, MP., Sukanto, MP. (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) UGP, 2025)
Gayo Arabica coffee is one of Indonesia's leading commodities with high economic value and is widely recognized in the international market for its distinctive flavor. Arabica coffee production is strongly influenced by various factors such as agro-ecological conditions, cultivation management, and harvest season dynamics. This study aims to estimate Arabica coffee production from farmers assisted by CV. Bintang Musara Rasa located in the Tanoh Gayo Highlands, covering Central Aceh Regency and Bener Meriah Regency. The research method used is a descriptive quantitative approach through field surveys (crop surveys) and interviews using structured questionnaires. Samples were taken at 10% of the total population of 723 assisted farmers, namely 75 farmers. Observations were conducted on 10 coffee trees per plantation, covering fruit age, number of production branches, levels of pest and disease attacks, and supporting data from collector interviews. The results showed that the average estimated production of ready-to-sell coffee (green bean ready) reached 1,196 kg/ha for one harvest, with the highest harvest distribution occurring from December to February. These results provide important contributions to the management of Arabica coffee production and distribution strategies in the Gayo region, particularly in the face of uneven harvest seasons.